2011
DOI: 10.5194/acp-11-1491-2011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, physical, and optical evolution of biomass burning aerosols: a case study

Abstract: Abstract. In-situ chemical composition measurements of ambient aerosols have been used for characterizing the evolution of submicron aerosols from a large anthropogenic biomass burning (BB) event in Israel. A high resolution Time of Flight Aerosol Mass Spectrometer (HR-RES-TOF-AMS) was used to follow the chemical evolution of BB aerosols during a night-long, extensive nationwide wood burning event and during the following day. While these types of extensive BB events are not common in this region, burning of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
109
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 52 publications
(64 reference statements)
13
109
2
Order By: Relevance
“…3, UV SSA values are nearly identical for the two cases while visible SSA is higher for the aged 17 April plume. A similar "brightening" at visible wavelengths with age was observed in field studies of biomass burning aerosol (Abel et al, 2003;Adler et al, 2011). Thus, the increase in AAE with plume age observed here is largely due to the decrease in absorption at visible wavelengths with time.…”
Section: Aerosol Oxidation and Spectral Absorptionsupporting
confidence: 60%
See 1 more Smart Citation
“…3, UV SSA values are nearly identical for the two cases while visible SSA is higher for the aged 17 April plume. A similar "brightening" at visible wavelengths with age was observed in field studies of biomass burning aerosol (Abel et al, 2003;Adler et al, 2011). Thus, the increase in AAE with plume age observed here is largely due to the decrease in absorption at visible wavelengths with time.…”
Section: Aerosol Oxidation and Spectral Absorptionsupporting
confidence: 60%
“…These findings may suggest that the oxidation of biomass burning OA primarily influences aerosol optical properties in the visible. This may, in part, be related to observed increases in particle size (and thus increased scattering at visible wavelengths) with age due to coagulation, water uptake, and condensation of gases (e.g., Grieshop et al, 2009a;Adler et al, 2011;Kondo et al, 2011), however changes to OA chemistry on a molecular level may also play a role. The similar UV SSA values between the aged 17 April plume and the fresh 29 June plume suggests similar amounts of UV absorption due to aerosols can be expected in fresh and aged plumes.…”
Section: Aerosol Oxidation and Spectral Absorptionmentioning
confidence: 99%
“…Quantifying the natural variations in biomass-burning aerosols is therefore necessary for accurate predictions. Previous studies of field and lab experiments show biomass-burning size distributions vary according to plume age, combustion phase, and fuel type (Adler et al, 2011;Capes et al, 2008;Hobbs et al, 2003;Hosseini et al, 2010;Janhäll et al, 2010;Okoshi et al, 2014). A review of observed size-distribution data by Janhäll et al (2010) shows the differences in modal width and median diameter as a function of fuel type (forest, savannah, grass), modified combustion efficiency, and plume age (fresh versus aged).…”
Section: Biomass-burning Particlesmentioning
confidence: 99%
“…These results suggest that during the forest fire event, the Oxidised Organics factor represented aerosol mass from the Biomass Burning factor that had 5 been processed through photochemical aging. Adler et al (2011) reported an OOA factor with a high F44 during a day following a massive forest fire event due to further oxidation processes. Furthermore, the organic signal profile of the Oxidised Organics factor in this study was highly comparable to the mass spectrum profile of the OOA-BB factor previously observed during a massive forest fire event in summer (Bougiatioti et al, 2014).…”
Section: Oxidised Organicsmentioning
confidence: 99%